Speech Adaptation of Personality as Focus of Psycho-linguistic Research - Zasekina, L. V. (Psychological Prospects Journal, 2011)
The structural and functional peculiarities of speech adaptation from perspective of levels of modern psycholinguistic methodology are considered in the article. The main structural components of speech adaptation are represented by cognitive phenomenological and linguistic structures. The main functions include integrative, reflective, regulative and instrumental impacts on personality lifeactivity. The results of experimental research show the increasing of volitional control, cognitive structures and functions of bilinguals as criteria of their effective speech adaptation.
Keywords: speech adaptation cognitive phenomenological linguistic structures integrative function reflective function regulative function instrumental function bilinguals monolingual